Hybrid FRP-timber thin-walled Cee section columns under axial compression: Numerical modelling. (December 2020) - Min, L.; Fernando, D.; Gilbert, B.P.; You, Zhong
Abstract: This study presents the first ever investigation aimed at accurate numerical modelling of the behavior of hybrid fibre reinforced polymer (FRP)-timber laminated (HFT) Cee section columns under axial compression. Existing numerical modelling approaches for modelling thin-walled structural members, such as modelling using composite laminate shell elements, orthotropic laminate shell elements with experimentally obtained properties, were found to either over-predict or under-predict the stiffness and capacity depending on the approach used. Existing modelling approaches fail to accurately capture the effects of possible interlaminar slips under combined flexural and axial loading. A new modelling approach using ABAQUS subroutine UGENS was proposed incorporating both in-plane stiffness matrix and bending stiffness matrix simultaneously, forming the general section stiffness matrix. Failure initiation criteria and a damage evolution law were incorporated in the subroutine to derive the damaged section stiffness matrix. The predictions from the proposed numerical model showed much improved agreement with the test results. Highlights: Existing numerical approaches for modelling laminated structures were found to be inadequate for modelling HFT Cee sections columns. Both axial and bending properties are important in modelling the behaviour of HFT Cee section columns. A numerical model considering different membrane and bending stiffnesses was developed to predict the behaviour of the HFT Cee section columns. Proposed numerical model was found to accurately capture the behaviour of HFT Cee section columns.